IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM PEMENUHAN STANDAR PENGELOLAAN PENDIDIKAN DI SMP NEGERI 1 PONTIANAK - F22211003, Saryana; ,, Aunurrahman; ,, Aswandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract:This research discuss about the implementation of school-based management in compliance with the standards of education management in SMP Negeri 1 Pontianak. The research is considered important and interesting to the researcher remembering that SMP Negeri 1 Pontianak applies zoning system in accepting the new students, but shows the excesses than the other schools, such as overall champion of PORSENI for four times in a row. The research aims to know about: the implementation of MBS seen from transparency, independency, cooperation, participation, and accountability principles in compliance with the standards of education management. The research uses the qualitative approach with the data source from the headmaster as the informant key which is supported by the other data such as, teachers, administration staffs, students parents / school committee, supervisors, founders, and also the functionary of Education Service of Pontianak. The data collecting was done by observing, deep interviewing, and documenting. The data analysis technique is interactive model from Miles and Huberman. From this research concluded: (1) transparency principle in compliance with the standards of education management in SMP Negeri 1 Pontianak has been implemented well, program plan and implemented program exposed to the school community and students parents; (2) independence principle in compliance with the standards of education management in SMP Negeri 1 Pontianak has been implemented in making curiculum, and also intern school independent; (3) cooperation principle in compliance with the standards of education management in SMP Negeri 1 Pontianak consists of cooperation between teachers in MGMP meeting and cooperation between school and the third side; (4) participation principle in compliance with the standards of education management in SMP Negeri 1 Pontianak by developing good communication with the full of solidarity. By making the teacher easy in presenting and approving the proposal and can increase the teachers participation in developing the school; (5) accountability principle in compliance with the standards of education management in SMP Negeri 1 Pontianak is done by involving the committee and parents to discuss the plan of school programs. The accountability reports of program are sent to the city education service, and be copied to school community. School-based management implementation should be done in every school, and the program plan and also implemented program are uploaded to school website. Key word: School-Based Management, Standard of Education Management Abstrak: Penelitian ini membahas mengenai implementasi manajemen berbasis sekolah dalam pemenuhan standar pengelolaan pendidikan di SMP Negeri 1 Pontianak. Penelitian ini dianggap penting dan menarik bagi peneliti mengingat SMP Negeri 1 Pontianak menerapkan sistem zoning dalam penerimaan siswa baru, namum menunjukkan kelebihan dibandingkan dengan sekolah lainnya, antara lain sebagai juara umum bidang PORSENI empat tahun berturut-turut. Penelitian ini bertujuan untuk mengetahui: implementasi manajemen berbasis sekolah dilihat dari prinsip transparansi, kemandirian, kerjasama, partisipasi, dan akuntabilitas dalam pemenuhan standar pengelolaan pendidikan di SMP Negeri 1 Pontianak. Penelitian ini menggunakan pendekatan kualitatif, sumber data yaitu, kepala sekolah sebagai key informan yang didukung dengan sumber lainnya, yakni: guru, tata usaha, siswa, orang tua siswa/ komite sekolah, pengawas pembina, serta pejabat dinas pendidikan Kota Pontianak. Pengumpulan data dilakukan dengan observasi, wawancara mendalam, dan dokumentasi. Teknik analisis data melalui model interaktif dari Miles dan Huberman. Dari penelitian ini disimpulkan: (1) prinsip transparansi dalam pemenuhan standar pengelolaan pendidikan di SMP Negeri 1 Pontianak terlaksana dengan baik, program yang telah terlaksana di paparkan kepada seluruh warga sekolah, komite sekolah dan orang tua siswa; (2) prinsip kemandirian dalam pemenuhan standar pengelolaan pendidikan di SMP Negeri 1 Pontianak, terlaksana antara lain dalam pembuatan kurikulum, rencana kerja sekolah, serta musyawarah guru mata pelajaran intern sekolah; (3) prinsip kerjasama dalam pemenuhan standar pengelolaan pendidikan di SMP Negeri 1 Pontianak meliputi kerjasama antara sesama guru dalam setiap pertemuan guru di sekolah, kerja sama antara sekolah dengan pihak ketiga; (4) prinsip partisipasi dalam pemenuhan standar pengelolaan pendidikan, dengan membangun komunikasi yang baik dengan penuh keakraban. Dengan mempermudah guru dalam mengajukan dan menyetujui proposal kegiatan, dapat meningkatkan partisipasi guru dalam memajukan sekolah; (5) prinsip akuntabilitas dalam pemenuhan standar pengelolaan pendidikan, di SMP Negeri 1 Pontianak dilakukan dengan cara melibatkan komite dan orang tua siswa dalam membahas rencana program sekolah. Laporan pertanggungjawaban pelaksanaan program dikirim ke dinas pendidikan kota, dan ditembuskan ke komite sekolah. Implementasi manajemen berbasis sekolah disarankan dilakukan di setiap sekolah, program yang telah diaksanakan dimasukkan dalam webside sekolah. Kata kunci : Manajemen Berbasis Sekolah